Pengendalian Akses Ruangan Menggunakan Nfc (Near Field Communication) Sebagai Kunci Pintu - Lugina Qolby Janari (Jur. Teknik Elektro Fak. Teknik UMY, 2016)

(untitled)
NFC (Near-Field Communication) is one of the development of technologies that have been there before, namely RFID (Radio Frequency Identification). NFC has the advantages in terms of data delivery is faster and can communicate in two ways. In addition, the NFC also has high security when sending data. The NFC as a technology that can be developed, can be applied on daily life by utilizing the features possessed of the NFC. One of the features is data that read by NFC can be used to controlling an access room. NFC combined with Arduino Uno as a controller, and the data was read by NFC will be recorded on a MicroSD that attached on Ethernet Shield.